How to do a Fistula tract Laser Closure (FiLaC) for trans‐sphincteric fistula‐in‐ano. Issue 6 (29th March 2021) - Suhardja, Thomas S.; Lim, James Tow‐Hing; Duieb, Zeev; Nguyen, Thang Chien; Teoh, William M. K.; Chouhan, Hanumant
Abstract : Sphincter‐preserving surgery for the treatment fistula‐in‐ano has always been an attractive option for complex fistulae where a significant proportion of the anal sphincter is involved. FiLaC™ is a promising approach due to its easy application, minimal side effects and preservation of functional outcome. Our center is an early adopter of FiLaC™ in Australia. We describe our approach to FiLaC™ for trans‐sphincteric fistula‐in‐ano in detailed steps.